A UNE e os partidos políticos no Governo Lula (2003-2010). - Paiva, Gabriel de Abreu Gonçalves de (2011)
This research examined the relationship of the National Union of Students (UNE) with the Lula government and the role of political parties in the entity during the period extending from 2003 to 2010. Based on authors such as Saldanha, Martins Filho, Bringel, we start from the assumption that the student movements for change are being mistaken to assign students a participation of a general nature and unchanging. After Lula s victory in the elections of 2002, UNE left the field of opposition to a collaborative relationship. Through the categories independence and democracy, our purpose was to understand the relationship of UNE with the government in preparation, proposing amendments and support to government projects. We used for this research, documents of the Congress of UNE, mainly theses defended by trends in youth political parties in the movement, programs and manifestation, of political parties that act in the entity; UNE documents that referred to the proposed policies on higher education; media news sources, reports the journal Movement, as well as documents and pamphlets of student movements. The testimonials and documents demonstrated the position of UNE, representing theoretical perspectives and policies that do not always appear explicitly, but when mediated by a conceptual framework, can help in understanding the positions taken by the entity. It was possible to understand from the testimonials and documents the role of UNE policy, implementation of government projects. Even before this fact the entity remained being fought by student trends, organized by political parties. Thus, we analyze the dispute between the parties within Congress UNE the direction of the entity. The final remarks demonstrate the process of cooptation by the State of UNE, seeking to demonstrate that their actions prove to be consistent with the policy taken by the Lula government. However, we point out the occurrence of a reorganization process of the students who challenged and broke with UNE.